Decline in antibiotic resistance and changes in the serotype distribution of Streptococcus pneumoniae isolates from children with acute otitis media; a 2001–2011 survey by the French Pneumococcal Network. (January 2015) - Kempf, M.; Varon, E.; Lepoutre, A.; Gravet, A.; Baraduc, R.; Brun, M.; Chardon, H.; Cremniter, J.; Croizé, J.; Dalmay, F.; Demachy, M.-C.; Fosse, T.; et al.
Abstract: Streptococcus pneumoniae is an important cause of acute otitis media (AOM). The aim of this study was to evaluate trends in antibiotic resistance and circulating serotypes of pneumococci isolated from middle ear fluid of French children with AOM during the period 2001–2011, before and after the introduction of the PCV-7 (2003) and PCV-13 (2010) vaccines. Between 2001 and 2011 the French pneumococcal surveillance network analysed the antibiotic susceptibility of 6683 S. pneumoniae isolated from children with AOM, of which 1569 were serotyped. We observed a significant overall increase in antibiotic susceptibility. Respective resistance (I+R) rates in 2001 and 2011 were 76.9% and 57.3% for penicillin, 43.0% and 29.8% for amoxicillin, and 28.6% and 13.0% for cefotaxime. We also found a marked reduction in vaccine serotypes after PCV-7 implementation, from 63.0% in 2001 to 13.2% in 2011, while the incidence of the additional six serotypes included in PCV-13 increased during the same period, with a particularly high proportion of 19A isolates. The proportion of some non-PCV-13 serotypes also increased between 2001 and 2011, especially 15A and 23A. Before PCV-7 implementation, most (70.8%) penicillin non-susceptible pneumococci belonged to PCV-7 serotypes, whereas in 2011, 56.8% of penicillin non-susceptible pneumococci belonged to serotype 19A. Between 2001 and 2011, antibiotic resistance among pneumococci responsible for AOM in France fell markedly, and PCV-7 serotypes were replaced by non-PCV-7 serotypes, especially 19A. We are continuing to assess the impact of PCV-13, introduced in France in 2010, on pneumococcal serotype circulation and antibiotic resistance.